The Role of English in the Business World for Import-Export Entrepreneurs: Insight from the Indonesian Furniture Industry - Muhammad Rizqi Setiawan; Sri Wahyuningsih (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2023)
In the era of globalization, communication or relations between countries, commonly referred to as international communication, is progressing in all countries. The role of English in the relations of a country is essential, especially in the business world, for example, the Import Export business, whose activities include importing and exporting goods from one country to another. This study aims to describe the roles of English in the world of import-export business in Indonesia, especially the furniture industry in Jepara Regency. This study employed a qualitative method. Data were collected from semi-structured interviews with an owner from the furniture Industry in Jepara, Indonesia, and several literature sources, research institutes, and government agencies. The findings reveal that English has an important role as an international communication tool and as a main to reach marketing. In addition, it is useful for building communication with people from various countries. Based on the results of this study, it can be concluded that the role of English is very crucial for a successful business, especially in terms of export-import with other countries.